Silencing of the tomato phosphatidylinositol‐phospholipase C2 (SlPLC2) reduces plant susceptibility to Botrytis cinerea - Gonorazky, Ana Gabriela (2016)
The tomato [Solanum lycopersicum (Sl)] phosphatidylinositol‐phospholipase C (PI‐PLC) gene family is composed of six members, named SlPLC1 to SlPLC6, differentially regulated on pathogen attack. We have previously shown that the fungal elicitor xylanase induces a raise of SlPLC2 and SlPLC5 transcripts and that SlPLC2, but not SlPLC5, is required for xylanase‐induced expression of defense‐related genes. In this work we studied the role of SlPLC2 in the interaction between tomato and the necrotrophic fungus Botrytis cinerea. Inoculation of tomato leaves with B. cinerea increases SlPLC2 transcript levels. We knocked‐down the expression of SlPLC2 by virus‐induced gene silencing and plant defense responses were analyzed upon B. cinerea inoculation. SlPLC2 silenced plants developed smaller necrotic lesions concomitantly with less proliferation of the fungus. Silencing of SlPLC2 resulted as well in a reduced production of reactive oxygen species. Upon B. cinerea inoculation, transcript levels of the salicylic acid (SA)‐defense pathway marker gene SlPR1a were diminished in SlPLC2 silenced plants compared to non‐silenced infected plants, while transcripts of the jasmonic acid (JA)‐defense gene markers Proteinase Inhibitor I and II (SlPI‐I and SlPI‐II) were increased. This implies that SlPLC2 participates in plant susceptibility to B. cinerea.